Nexus Between Poverty and Access to Essential Service Centers in Education, Health, and Markets - Acharya, Krishna Prasad (Management Dynamics, 2023)
Among the service offering firms, education, health and market are the most important centers. The accessibility of these centers, if made easy, then the life style of people may be uplifted, and on the contrary, may decline when there is limited accessibility to those centers resulting into increased poverty. In this study, the sample from 5,988 households of Nepal Living Standard survey 2010/11 has been taken. This study incorporates analysis done through Descriptive statistics and consumption quintile group. The maximum time taken to reach higher secondary school is the highest (1920 minutes) from any particular house followed by the maximum time taken to reach public hospital/primary health care (PHC) and market center (1440 minutes). It takes three to six times more to reach social service centers in rural areas than in urban areas. It takes double time to reach the market center in Hill than in Terai, and almost 4 times in Mountain than in Terai. Also, the odds of household being poor in within the reach of 30 minutes is lower compared to that of beyond the reach of 30 minutes. The odds of household being poor of beyond the reach of 30 minutes is almost the double of within the reach of 30 minutes. From the quintile consumption groups, the male literacy rate of poorest quintile is approximately the double of the female literacy rate of poorest quintile group. This study found out that there is a direct negative relationship between social service centers and walking distance. It is concluded that as per capita expenditure quintile goes up from poorest to richest, the walking distance time decreased. Hence, the findings of the study advise the policy makers to boost the amount of money invested in infrastructure, health care, and education to reduce the poverty in Nepal.